Martial Arts Participation, Aggression, and Self-Control: An Examination of the “Gentle Arts.” - Wilkinson, Matthew (Journal of Amateur Sport, 2023)
The recent emergence of mixed-martial arts (MMA) as a professional sport has led to an increased interest in martial arts in the United States. While the visibility of the violence that constitutes mixed martial arts might be cause of concern, MMA is not indicative of martial arts participation as a whole. The martial arts have become an increasingly popular form of leisure that draws a broad, diverse group of participants. This study explores the relationships between martial arts participation, aggression, and self-control. Using the Buss-Perry Aggression Questionnaire (BPAQ) (1992) and Tangney’s Brief Self-Control Scale (BSCS) (2004), my findings show that compared to non-participants, individuals who participate in martial arts training are less verbally aggressive, less hostile, less angry, and exhibit more self-control.